2020
DOI: 10.1038/s41416-020-01114-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic aberrations in DNA repair pathways: a cornerstone of precision oncology in prostate cancer

Abstract: Over the past years, several studies have demonstrated that defects in DNA damage response and repair (DDR) genes are present in a significant proportion of patients with prostate cancer. These alterations, particularly mutations in BRCA2, are known to be associated with an increased risk of developing prostate cancer and more aggressive forms of the disease. There is growing evidence that certain DDR gene aberrations confer sensitivity to poly-(ADP ribose) polymerase inhibitors and/or platinum chemotherapy, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 90 publications
3
79
0
3
Order By: Relevance
“…Cytotoxic chemotherapy causes severe DNA damage directly by induction of breaks or indirectly due to the formation of reactive oxygen species (ROS) and ultimately induce cell death 34,35 . In responses to DNA damage, cells recruit DNA repair factors to upregulate mutagenic repair pathways that to maintain survival 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Cytotoxic chemotherapy causes severe DNA damage directly by induction of breaks or indirectly due to the formation of reactive oxygen species (ROS) and ultimately induce cell death 34,35 . In responses to DNA damage, cells recruit DNA repair factors to upregulate mutagenic repair pathways that to maintain survival 36 .…”
Section: Discussionmentioning
confidence: 99%
“…This is the threshold point at the start of "prostate reprogramming" and the "loss" of cell function, homeostasis and regulation pathways [192][193][194][195][196][197]. It marks the beginning of a prostate stagnation tumorigenesis inflammatory microenvironment with heterogeneous events [17] including inflammation [57, [140][141][142]198], genetic aberrations [199][200][201][202][203][204][205], epigenetic dysregulation [206][207][208][209][210], autophagy dysregulation [86,87,89,90,[211][212][213][214][215][216] and lysosomal dysfunction [217][218][219][220].…”
Section: Evolutionary Tumorigenesis Microenvironmentmentioning
confidence: 99%
“…Alterations in DNA damage repair (DDR) genes, such as those involving the homologous recombination (HR) pathway genes, such as BRCA2, BRCA1, ATM, CDK12 , and PALB2 , occur in approximately 20–25% of mCRPC cases at either the somatic or the germline level [ 27 , 28 ]. In this regard, two Poly (ADP-ribose) polymerase inhibitors (PARPi), rucaparib and olaparib, have been recently approved by the FDA for the treatment of mCRPC [ 29 ].…”
Section: Current Treatment Options For Metastatic Castration-resistant Prostate Cancer (Mcrpc)mentioning
confidence: 99%
“…Interestingly, defects in HR pathway genes may also be associated with an increase in genomic instability, neoantigen load, PD-L1 expression, and tumor-infiltrating lymphocytes [ 120 ]. Alterations in HR pathway genes, including BRCA2 , BRCA1 , ATM , CDK12 , and PALB2 , occur in approximately 20–25% of mCRPC cases at either the somatic or the germline level [ 27 , 28 ], making these patients potentially more responsive to ICIs and suggesting that HR pathway genes may be potential predictive biomarkers of response to ICIs. Indeed, several studies, including the KEYNOTE-199 and CheckMate-650 trials, have shown a trend towards a higher ORR to pembrolizumab in HR-deficient mCRPC patients [ 59 , 72 ].…”
Section: Mechanisms Of Resistance and Potential Predictive Biomarkers Of Ici Responsementioning
confidence: 99%